2013
DOI: 10.5812/archcid.15983
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Contamination of Raw Vegetables in Amol, North of Iran

Abstract: Background:One of the most important ways of pathologic and non-pathologic parasites transmission is through eating raw vegetables. Iranian people believe that eating raw vegetables is an important way to get some essential vitamins and minerals. Objectives: According to the high prevalence of pathologic parasites and also exporting different vegetables to the other provinces such as Tehran, we conducted this study to evaluate the parasitic pollution of raw vegetables in Amol city. Materials and Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 5 publications
3
21
0
Order By: Relevance
“…In our study we observed a significant association of seropositivity with the consumption of undercooked meat and unwashed raw vegetables. The latter are one of the main sources of parasitic infections in Northern Iran and around the world 27 , 28 . Several studies claimed that consumption of undercooked meat is an important factor for parasite transmission 12 , 15 , 17 , 24 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study we observed a significant association of seropositivity with the consumption of undercooked meat and unwashed raw vegetables. The latter are one of the main sources of parasitic infections in Northern Iran and around the world 27 , 28 . Several studies claimed that consumption of undercooked meat is an important factor for parasite transmission 12 , 15 , 17 , 24 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…1,[10][11][12] Studies conducted on various items of fruit and vegetable samples have shown that Ascaris lumbricoides, Cryptosporidium spp, Entamoeba histolytica, Enterobius vermicularis, Fasciola spp, Giardia lamblia, hookworms, Hymenolepis spp, Taenia spp, Trichuris trichiura, Cyclospora spp, and Toxocara spp infect humans who consume contaminated fruits and vegetables without cooking or washing them properly. 1,4,[13][14][15][16] Epidemiological studies indicated that the number of reported cases of foodborne illnesses due to consumption of raw fruits and vegetables has been increasing and continues to be a common and serious threat to public health in endemic areas for IPs. 10,15,17 Fruits and vegetables can become contaminated with parasitic pathogens throughout the process from planting to consumption.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Siyadatpanah et al reported that the rate of nematode larvae on raw vegetables was 25.8% in Amol, North of Iran. [19] In another study, the low frequency of free-living larvae contamination (7%) was reported in vegetables consumed in Malayer city, West of Iran. [20] Parasite contamination in vegetables has also been reported in several countries such as Turkey (36%) and Nigeria (5.9%).…”
Section: Discussionmentioning
confidence: 94%